Closing the Class Gap in Civic Participation - Fried, Amy (Maine Policy Review, 1999)
In the Margaret Chase Smith essay, Amy Fried discusses the implications of increasing class stratification on civic participation in the United States. She suggests that public schools can play an important role in improving citizen engagement.
Keywords: social stratification; civic participation